ECONOMIC DEVELOPMENT. A HISTORICAL - NEOINSTITUTIONAL APPROACH OVERVIEW - MORSELLI, Alessandro (Theoretical and Practical Research in Economic Fields, 2020)
This paper aims to investigate economic development through a historical-neoinstitutional approach, to improve the understanding of the process of economic change. It will try to demonstrate how the intervention of the institutions can trigger a virtuous circle able to reduce transaction costs, facilitate the dissemination of information, in order to make the functioning of the economy more efficient. In this sense, economic change is identified as an intentional process triggered by the combination of the beliefs and preferences of individuals. All this takes place through the intervention of rules, procedures and organizations. This scenario differs from that represented by the neoclassicists, both for the importance given to the market, to companies and other organizations linked to the institutional environment, and for the importance given to transaction costs. In this regard, the reasons for the existence of institutions such as companies and hierarchical organizations have been researched. The survey will therefore focus on the importance of the link between institutions and economic development, in order to achieve an improved understanding of the process of economic change.